Mechanisms Underlying Lysosomal Dysfunction in Atherosclerotic Plaque Macrophages - Ferreira, Inês Sofia da Silva (2022)
Atherosclerosis is a chronic inflammatory disease mainly defined by the sequestration of lipids by macrophages in the interior of the artery wall. This pathology is the primary cause of most cardiovascular diseases (CVD). Development of atherosclerosis involves the accumulation of low-density lipoprotein (LDL) in the arterial intima. A main component of LDL are poly-unsaturated cholesteryl esters that are susceptible to oxidation contributing to the formation of oxidized-LDL (ox-LDL). After uptake, ox-LDL are digested in the lysosomes of macrophages. However, macrophages exposed to ox-LDL become unable to digest these particles, due to lysosomal dysfunction, originating foam cells, and contributing to lesion progression. Our group identified a family of oxidized lipids termed cholesteryl hemiesters (ChE) in plasma of CVD patients. The most prevalent lipid of this family is cholesteryl hemiazelate (ChA). Interestingly, exposure to this lipid is sufficient to cause lysosome dysfunction in macrophages. In this study, we aim to clarify the molecular mechanism that leads to lysosomal dysfunction in mouse macrophages (RAW 264.7) upon exposure to ChA by studying the role of transcription factors that regulate lysosomal biogenesis. Here we aspire to determine through immunocytochemistry and cell fractionation followed by Western blot techniques which transcription factor is translocated to the nucleus in immortalized murine macrophages when exposed to ChA. Additionally, we aim to characterize the lysosomal phenotype caused by ChA in a macrophage cell line in which the gene expression of Tfeb and Tfe3 has been deleted by CRISPR/Cas9 technology. Kinetics experiments showed translocation of the TFs to the nucleus, at 24 and 48h for TFE3 and 48 and 72h for MITF in ChA-treated RAW Null (wild-type) macrophages. Furthermore, in RAW TFEB/TFE3 deficient cells (RAW dKO) exposed to ChA, we observed a delay in the development of lysosomal enlargement and a decrease in lysosomal number indicating the involvement of these transcription factors in these outcomes.